Cursing in the American Animated Sitcoms “Family Guy”: A Pragmatic Study - Faisal, Asst. Prof. Wafaa Mukhlus; Alwan, Asmaa Amjad (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This study examines the pragmatic function of cursing in the American animated sitcom Family Guy, analyzing how various speech acts and impoliteness strategies influence character interactions and contribute to the show's comedic and dramatic elements. Through Speech Act Theory (Searle, 1969), Culpeper’s Impoliteness Strategies (1996), and Grice’s Implicature Theory (1975), the analysis demonstrates that cursing serves multiple communicative purposes, including expressing frustration, asserting dominance, enforcing commands, and reinforcing humor. Speech acts such as expressives, directives, commissives, and assertives shape how characters employ cursing to heighten emotional intensity and narrative realism. Impoliteness strategies further reveal how cursing functions as a tool for aggression, power assertion, and relational tension, intensifying confrontations through bald-on-record impoliteness, sarcasm, and autonomy threats. Grice’s Implicature Theory highlights the underlying meaning in curse-laden exchanges, showing how implied insults, exaggeration, and irony strengthen character dynamics and comedic delivery. The findings suggest that Family Guy strategically uses cursing as a linguistic device that enhances storytelling, humor, and character development while reflecting exaggerated social interactions. This study contributes to understanding the role of offensive language in animated sitcoms, demonstrating its impact on viewer engagement and narrative construction.